Green Financing Practices in India’s Renewable Energy Sector: A Study - Sohail PERWEZ; Syed Khaja SAFIUDDIN (PT Keberlanjutan Strategis Indonesia, 2025)
India's goals of attaining 500 GW of renewable energy capacity by 2030, as part of its Panchamrit climate commitments, require a significant financial transformation. Addressing the projected annual funding deficit of INR 11 lakh crores (USD 170 billion) is essential for the expansion of renewable initiatives, including solar, wind, and hydro energy projects. This study examines the present state of green finance in India, highlighting the significance of instruments such as sovereign green bonds, blended finance, green banks, and crowdfunding in facilitating the growth of renewable energy.The research employs exploratory analysis of governmental data, policy documents, and multilateral sources to identify critical structural impediments, including inadequate enforcement of Renewable Purchase Obligations (RPOs),underdeveloped debt markets, minimal foreign direct investment (2.05%), and disjointed regulatory frameworks. Research indicates that while entities like IREDA and programs such as viability gap funding (VGF) have stimulated solar expansion, overarching market inefficiencies remain.Merely 34% of public sector banks actively endorse renewable energy, whereas the involvement of foreign banks is minimal.The paper additionally delineates investor engagement and quantifies sector-specific fund distributions, highlighting that solar energy commands the largest proportion (34.58%), followed by hydro and wind energy.The study highlights the critical necessity for a varied financing ecosystem, incorporating ESG-linked bonds, credit guarantee frameworks, and improved public-private collaborations.The paper promotes enhanced adherence to RPOs, the development of innovative financing models, and the implementation of strategic de-risking mechanisms to bolster investor confidence.These initiatives are crucial for expediting India’s energy transition, fulfilling Sustainable Development Goal 7, and significantly aiding global climate objectives.